Rudimentary horn pregnancy: a rare entity - Jacob, Sujamol; Karunakaran, Lalithambica; Devasia, Neena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Unicornuate uterus is the type 2 variety of mullerian duct anomaly resulting in unilateral agenesis or hypoplasia. The hypoplastic (Rudimentary) horn can be functioning or non-functioning and communicating or noncommunicating with the main uterine cavity. Pregnancy in the rudimentary horn is an extremely rare entity. It is often missed at ultrasound in the early trimester, presenting later with massive hemoperitoneum and shock from rupture of the horn. A “high index of suspicion” is essential to derive at the correct diagnosis. Hence reporting this rare case for emphasizing the importance in early diagnosis and prompt management.